Managing Corneal Infections: Out with the old, in with the new? - Sanjay Marasini; Jennifer P. Craig; Simon J. Dean; Leon G. Leanse (MDPI AG, 2023)
There have been multiple reports of eye infections caused by antibiotic-resistant bacteria, with increasing evidence of ineffective treatment outcomes from existing therapies. With respect to corneal infections, the most commonly used antibiotics (fluoroquinolones, aminoglycosides, and cephalosporines) are demonstrating reduced efficacy against bacterial keratitis isolates. While traditional methods are losing efficacy, several novel technologies are under investigation, including light-based anti-infective technology with or without chemical substrates, phage therapy, and probiotics. Many of these methods show non-selective antimicrobial activity with potential development as broad-spectrum antimicrobial agents. Multiple preclinical studies and a limited number of clinical case studies have confirmed the efficacy of some of these novel methods. However, given the rapid evolution of corneal infections, their treatment requires rapid institution to limit the impact on vision and prevent complications such as scarring and corneal perforation. Given their rapid effects on microbial viability, light-based technologies seem particularly promising in this regard.